A classe une, o gênero separa: mulheres no comando dos sindicatos da educação e as relações de gênero - Dantas, Adenilde de Souza (2023)
This research aims to examine the career paths of women who have held or currently hold the position of president in education unions, with a focus on gender and power relations and the development of identities. The theoretical framework for this analysis is based on the historicaldialectical materialism approach in conjunction with feminist and gender theories, and guides the analysis of this research object, which is centered on the Brazilian Basic Education trade unionism context’s gender relation. The qualitative methodology proved to be effective, particularly for exploring the thematic field, by consulting various sources of information, such as literature review/bibliographical survey; documents from Capes (Coordination of Improvement of Higher Education Personnel) Thesis and Dissertation Database and its Portal of Journals to map relevant national and international studies on women in command of teachers’ unions; observation of union activities and news collected virtually from all five Northern region unions’ official websites, social networks (Instagram, Facebook and TikTok) along with YouTube videos on their activities. Trade union documents, including the last fiveyear conference agendas, union handbooks, bylaws, and standing rules, were reviewed to uncover their political perspectives. Updated lists of the executive boards of education unions were also consulted. The research included interviews with eight women, grouped into two categories: a) five presidents of education unions in Northern Brazil, and b) two former leaders and one current leader of the National Confederation of Education Workers (CNTE). The interviews, conducted over the Google Meet and Zoom virtual platforms, were recorded, transcribed, and then analyzed. Content analysis, as a dynamic methodology, was demonstrated to be relevant in guiding the data analysis. Research findings indicate an increase in the number of women leading educational trade unions, especially in the northern region of Brazil. This fact, according to the subjective data, is attributed to the growing discussions surrounding more female participation both in social life and within decision-making and power spaces, facilitated by feminist organizations, and by central trade union women’s bureaus, associations, trade unions, and political parties. In this regard, the CNTE’s political role is notable for establishing a gender policy that seeks to empower women within unions through the development and establishment of spaces for discussing issues related to the women’s agenda in various forums such as magazines, courses, workshops, meetings, conferences, and congresses. Additionally, the CNTE recommends that its affiliated unions establish gender or women’s secretariats/departments/directories, thus encouraging the formation of women’s collectives and the implementation of policies related to race, LGBTQIAPN+, etc. Nevertheless, in the majority of education trade unions in Brazil, there is still female underrepresentation in positions of power, considering the number of women in Basic Education. The research findings indicated that this is due to male chauvinism and its perpetuation by women both within and outside the unions, disbelief regarding women’s abilities in performing tasks, workplace harassment, and challenges in balancing productive and reproductive work, especially in caring for small children. This has repercussions, for example, on the absence of women with small children at the highest levels of trade union power. In addition, it became evident that the context, the political-union conjuncture and the relationships established amongst the individuals directly interfere with the choice of names for male / female presidents. In this regard, female support and unity are fundamental to empowering other women.